Land evaluation, characterization and classification of soil for the proposed oil palm plantation in Ekpri Ibami, Akamkpa Local Government Area, Nigeria - John, Kingsley; Akpan-Idiok, Ackley Ufot (International Journal of Environment, Agriculture and Biotechnology, 2019)
Land evaluation, characterization and classification of soil for the proposed oil palm plantation in Ekpri Ibami, Akamkpa Local Government Area, Nigeria was conducted on 50 ha of land using a combination of both conventional and digital survey methods. The objective of the research was to characterize, classify and evaluate the land for the proposed oil palm production. Three soil mapping units were identified (EKP I, EKP II and EKP III) and representative profile pits were dug in each mapping unit. Samples were collected from each pedogenic horizon. Soils morphological, physical and chemical properties were determined using appropriate methods. Results revealed that soils of all of the mapping are characterized by dark greyish brown colour with thin topsoil while yellowish red to strong brown mottles were observed at the subsoil. The soils are coarsed-textured with high sand, low silt, and clay fractions. The soils were strong to moderately acidic (4.8 to 5.3). The soils also have low inherent of natural fertility with low organic carbon content, total nitrogen, and moderately available phosphorus. Low effective cation exchange capacity and high base saturation which may have occurred in available forms in solutions in spite of the low cation reserves in the soil. The individual mapping units were classified as Arenic Eutrudept, Typic Hapludult and Aquic Paleudults for EKP I, EKP II and EKP III respectively. The land was then evaluated and classified based on its suitability for oil palm production. Parametrically, mapping units EKP I and EKP II were marginally suitable and EKP III not suitable for the proposed oil palm production. Non-parametrically, EKPI is moderately suitable, EKP II is marginally suitable and EKP III is not suitable, for growing oil palm. The prevailing limitations on the Ekpri Ibami landscape for oil palm production include fertility, wetness, and topography and soil physical properties. Fertility factor happened to be the most limiting factor in all the mapping units. And thus can be ameliorated through the application of organic manures, NPK fertilizer and liming to improve the nutrient status of the soil.